Effect of La2O3 content on the oxygen barrier ability of the HfB2‐SiC coating at 1973 K. Issue 3 (17th November 2022) - Qian, Deyu; Chen, Yuexing; Ren, Xuanru; Wang, Leyu; Chen, Jiaping; Zhao, Yan; Shi, Dalin; Li, Yuan; Du, Haobo; Feng, Peizhong
Abstract: To inhibit the destructive evolution of the HfB2 ‐SiC coating during oxidation, La2 O3 was added to modify the oxygen‐blocking capability of the HfB2 ‐SiC coating. The effect of La2 O3 content on the oxygen barrier capacity of HfB2 ‐SiC was investigated. The addition of 5 vol.% La2 O3 lowered the oxidation activity and strengthened the inert oxygen barrier capacity of the HfB2 ‐SiC coating, which made the oxygen permeability and maximum weight change rate of the coating decrease by 30.32% and 73.97%, respectively. Due to the solid solution reaction of the dispersed La2 O3, HfO2, and SiO2 nanoparticles, a stable Hf‐B‐La‐Si‐O multiphase glass was formed on the surface of the coating. Besides, the high‐melting‐point particles, such as HfO2, La2 Hf2 O7, and HfSiO4, dispersed in the glass layer as hard particles and formed a mosaic structure based on the Hf‐B‐La‐Si‐O compound, which increased the cumulative protection efficiency of the HfB2 ‐SiC coating to 98.5% and reduced the inert factor value by 84.57%. However, the excessive consumption of SiO2 glass by La2 O3 results in dendritization of the generated glass when the La2 O3 content is above 10 vol.%, which reduced the self‐healing capability of the generated glass and instead weakened the oxygen barrier properties of the HfB2 ‐SiC‐La2 O3 coatings.